2015
DOI: 10.1021/acs.nanolett.5b02582
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Purification of Silver Nanowires To Make Conducting Films with a Transmittance of 99%

Abstract: Metal nanowire (NW) networks have the highest performance of any solution-coatable alternative to ITO, but there is as yet no published process for producing NW films with optoelectronic performance that exceeds that of ITO. Here, we demonstrate a process for the synthesis and purification of Ag NWs that, when coated from an ink to create a transparent conducting film, exhibit properties that exceed that of ITO. The diameter, and thus optoelectronic performance, of Ag NWs produced by a polyol synthesis can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
311
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(320 citation statements)
references
References 33 publications
8
311
0
Order By: Relevance
“…15 To start, 2.45 g of polyvinylpyrrolidone (PVP) was added to 60 ml of ethylene glycol (EG) and heated to solution was injected into the reactant. Then, 7.65 ml of 0.654 M silver nitrate solution was introduced into the reactant.…”
mentioning
confidence: 99%
“…15 To start, 2.45 g of polyvinylpyrrolidone (PVP) was added to 60 ml of ethylene glycol (EG) and heated to solution was injected into the reactant. Then, 7.65 ml of 0.654 M silver nitrate solution was introduced into the reactant.…”
mentioning
confidence: 99%
“…[39][40][41][42] The performance of the metal NW-based electrode generally increases with the decrease in the diameter of the NW, while the increase in the NW length/diameter aspect ratio will reduce light scattering and decrease the resistance in the film. [43][44][45][46][47][48][49] Therefore, in this study, Ag NWs with an average aspect ratio of 5000 (average diameter of B30 nm and length of 100-200 um, Fig. S1, ESI †) were utilized as the transparent and conductive front-electrodes in the flexible CQD solar cells.…”
Section: Solution-processed Flexible Electrodementioning
confidence: 99%
“…These features make them ideal for use as transparent electrodes for flexible devices. [8][9][10][11][12][13]17,18 However, for device applications, some issues related to the fabrication of Ag NW network 2D films still need to be solved; these issues include the fact that they are easy to oxidize 15 and are subject to haziness due to light scattering 14 by the uneven surfaces of thick Ag NWs because constructing conductor films that have a junction between NW networks. In particular, in terms of the optical performance, their haze value is generally lower.…”
Section: Introductionmentioning
confidence: 99%
“…These studies were mainly focused on controlling the size, shape, crystal structure, and optical and electrical properties of the Ag NWs. Recently, Wiley et al 17 reported that Ag NWs with diameters of approximately 20 nm and aspect ratios up to 2000 can be synthesized by optimizing the bromide ion concentration used in the conventional polyol method. Our group has also contributed to this field of study by reporting on thin Ag NWs with an average diameter of 20 nm and length of 22 µm, which were developed using a pressure-induced polyol method.…”
Section: Introductionmentioning
confidence: 99%